Antibiotic Use, Antibiotic Resistance, and Antibiotic Stewardship – A Global Public Consequences (Bangladesh Journal of Medical Science, 2019)
Abstract not availableBangladesh Journal of Medical Science Vol.18(2) 2019 p.169-170